The Association Between the Frequency of Annual Health Checks Participation and the Control of Cardiovascular Risk Factors - Lei, Li; Tang, Yongzhen; Zhang, Qiuxia; Xiao, Min; Dai, Lei; Lu, Junyan; Lin, Xinxin; Lu, Xiangqi; Luo, Wei; Pan, Jiazhi; Xin, Xiaoyu; Qiu, Shifeng; et al. (Frontiers in Cardiovascular Medicine, 2022)
Background General health checks can help in controlling cardiovascular risk factors. However, few studies have investigated whether regular participation in annual health checks could further improve the control of cardiovascular risk factors compared with intermittent participation. Therefore, our study aimed to explore the association between the frequency of annual health check participation and the control of cardiovascular risk factors. Methods Residents aged ≥ 65 years or having chronic diseases (hypertension or diabetes) from 37 communities of Guangzhou, Guangdong, who participated in the Basic Public Health Service project between January 2015 and December 2019, were enrolled and divided into 3 groups (“Sometimes,” “Usually,” and “Always”) according to their frequencies of annual health check participation. Multivariable linear regression models were performed to assess the association between the frequency of annual health check participation and the control of cardiovascular risk factors. A subgroup analysis stratified by gender was also conducted. Results In total, 9,102 participants were finally included. Significant differences were identified between groups in systolic blood pressure (SBP), diastolic blood pressure (DBP), weight, fasting glucose, total cholesterol, high-density lipoprotein cholesterol, and serum creatinine. After fully adjusting for confounding factors, residents who always participated in the annual health check tended to have lower SBP (β = −4.36, 95% CI: −5.46; −3.26, p < 0.001), fasting glucose (β = −0.27, 95% CI: −0.38; −0.15, p < 0.001), and total cholesterol (β = −0.19, 95% CI: −0.26; −0.13, p < 0.001), compared with those who attended sometimes. Furthermore, gender did not alter these associations. Conclusion A higher frequency of annual health check participation was associated with lower SBP, fasting glucose, and total cholesterol.